2021
DOI: 10.1111/ijlh.13760
|View full text |Cite
|
Sign up to set email alerts
|

Impact of COVID‐19 pandemic on the quality of test output in haemostasis laboratories

Abstract: The spread of severe acute respiratory syndrome coronavirus 2 (SARS CoV-2) started in Wuhan (Hubei Province, People's Republic of China) 1 and led to the pandemic outbreak of coronavirus disease 2019 (COVID-19) at the start of 2020. 2 This outbreak had an enormous impact on the healthcare services worldwide. 3,4 The COVID-19 pandemic also affected medical laboratories. 3 Haemostatic laboratories experienced a major rise in testing requests even though non-COVID, scheduled health care decreased. 4 The reason fo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
2
1

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(1 citation statement)
references
References 27 publications
0
1
0
Order By: Relevance
“…From the recent citations, Arisz and colleagues evaluated the quality of test output in hemostasis laboratories due to COVID-19, which had caused a surge in testing, inclusive of D-dimer testing. 12 They conducted a questionnaire that identified that many laboratories reported a large increase of >25% in the number of test requests for anti-Xa, D-dimer, and fibrinogen assays in 2020 compared with 2019. Despite this testing increase, no differences in response rate or the quality of the measurements were observed between EQA surveys from 2019 to 2020.…”
Section: Discussionmentioning
confidence: 99%
“…From the recent citations, Arisz and colleagues evaluated the quality of test output in hemostasis laboratories due to COVID-19, which had caused a surge in testing, inclusive of D-dimer testing. 12 They conducted a questionnaire that identified that many laboratories reported a large increase of >25% in the number of test requests for anti-Xa, D-dimer, and fibrinogen assays in 2020 compared with 2019. Despite this testing increase, no differences in response rate or the quality of the measurements were observed between EQA surveys from 2019 to 2020.…”
Section: Discussionmentioning
confidence: 99%